EKSISTENSI ALBUM LAGU UNTUK DUNIA, CINTA, DAN KOTORNYA KARYA NADIN AMIZAH: KAJIAN EKSISTENSI KIERKEGAARD - Taninda Mey Tantika; Yarno; Suher (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2025)
The phenomenon of a person's existential crisis is becoming increasingly complex in the modern era. Anyone has the right to fight for their existence, including a singer. The purpose of this research is to find the existence of the song album For the World, Love, and Dirty by Nadin Amizah. To deepen the meaning of existence, the researcher uses Soren Kierkegaard's theory of existentialism. This study uses a qualitative descriptive method. The data source used by the researcher is in the form of song lyrics on the album. The data collection technique is by studying documents by studying song lyrics to identify aesthetic, ethical, and religious existence. The results of this study show that Nadin describes the three stages of existence in the album of the song Untuk Dunia, Love, and Dirtynya. On an aesthetic level, there is an attitude of freedom without regard for morals. Then, enter the phase of emotional maturity in accordance with responsibility at the ethical stage. Then, it is perfected at the religious stage, that is, surrender to God.